2018
DOI: 10.1126/science.aat5397
|View full text |Cite
|
Sign up to set email alerts
|

The hippocampal engram maps experience but not place

Abstract: Episodic memories are encoded by a sparse population of hippocampal neurons. In mice, optogenetic manipulation of this memory engram established that these neurons are indispensable and inducing for memory recall. However, little is known about their in vivo activity or precise role in memory. We found that during memory encoding, only a fraction of CA1 place cells function as engram neurons, distinguished by firing repetitive bursts paced at the theta frequency. During memory recall, these neurons remained hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
144
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(170 citation statements)
references
References 29 publications
(25 reference statements)
18
144
0
1
Order By: Relevance
“…94 We then quantified the relationship between calcium activity and IEG expression. Consistent with 95 previous reports (Tanaka et al, 2018;Yassin et al, 2010), we found that average calcium activity 96 correlated positively with expression levels recorded 34 to 42 minutes later for both Arc and c-Fos (Figure 97 1E). The cross-correlation between neural activity and IEG expression levels was increased and relatively 98 stable over a broad range of time lags between neural activity and IEG expression measurement (Figure 99 S1C).…”
supporting
confidence: 88%
“…94 We then quantified the relationship between calcium activity and IEG expression. Consistent with 95 previous reports (Tanaka et al, 2018;Yassin et al, 2010), we found that average calcium activity 96 correlated positively with expression levels recorded 34 to 42 minutes later for both Arc and c-Fos (Figure 97 1E). The cross-correlation between neural activity and IEG expression levels was increased and relatively 98 stable over a broad range of time lags between neural activity and IEG expression measurement (Figure 99 S1C).…”
supporting
confidence: 88%
“…Consistent with this notion, our estimates of significantly CS-selective cells that emerge with learning fall within the range of the 10-20% of CA1 pyramidal neurons recruited in engrams supporting hippocampal-dependent memory [Tayler et al, 2013, Tanaka et al, 2018, Rao-Ruiz et al, 2019]. If the sparse subset of CS-selective cells we observe do represent engram cells, then this would further support the notion that gating mechanisms exist to ensure sparsity of encoded engrams, since the size of the engram does not vary with behavioral paradigms, such as immobilized, auditory tFC used here compared with contextual learning in freely moving animals [Rao-Ruiz et al, 2019].…”
Section: Discussionsupporting
confidence: 66%
“…These units encode cue information in a learning-dependent manner. It is plausible that these dynamics may relate to descriptions of hippocampal memory “engram cells”, identified via immediate early gene (IEG) products [Liu et al, 2012, Vetere et al, 2017, Tanaka et al, 2018, Rao-Ruiz et al, 2019].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, all 3 types of place cells displayed a shift towards the descending wave with learning, though this shift was greatest in remapping cells. Recently, a place cell study of engram cells 42 in the mouse hippocampus showed that when engram cells fire bursts of action potentials, they tend to do so on the descending wave of theta 43 , lending support to our findings and suggesting that the remapping cell population may overlap with that of engram cells.…”
Section: Inputs Driving Remappingsupporting
confidence: 86%